Cell‐Based Proteome Profiling Using an Affinity‐Based Probe (AfBP) Derived from 3‐Deazaneplanocin A (DzNep). Issue 8 (7th June 2013) - Tam, Eric K. W.; Li, Zhengqiu; Goh, Yi Ling; Cheng, Xiamin; Wong, Sze Yue; Santhanakrishnan, Sridhar; Chai, Christina L. L.; Yao, Shao Q.
Abstract 3‐Deazaneplanocin A (DzNep), a global histone methylation inhibitor, has attracted significant interest in epigenetic research in recent years. The molecular mechanism of action and the cellular off‐targets of DzNep, however, are still not well‐understood. Our aim was to develop novel DzNep‐derived small‐molecule probes suitable to be used in live mammalian cells for identification of potential cellular targets of DzNep under physiologically relevant settings. In the current study, we have successfully designed, synthesized, and tested one such probe, called Dz-1. Dz-1 is a 'clickable' affinity‐based probe (AfBP) derived from DzNep with minimal structural modifications. The probe was found to be highly cell‐permeable, and possessed similar anti‐apoptotic activities as DzNep in MCF‐7 mammalian cells. Two additional control probes were made as negative labeling/pull‐down probes in order to minimize false identification of background proteins due to unavoidable, intrinsic nonspecific photo‐crosslinking reactions. All three probes were subsequently used for in‐situ proteome profiling in live mammalian cells, followed by large‐scale pull‐down/LC‐MS/MS analysis for identification of potential cellular protein targets that might interact with DzNep in native cellular environments. Our LC‐MS/MS results revealed some highly enriched proteins that had not been reported as potential DzNep targets. These proteins might constitute unknown cellular off‐targets of DzNep. Though further validation experiments are needed in order to unequivocally confirm these off‐targets, our findings shed new light on the future use of DzNep as a validated chemical probe for epigenetic research and as a potential drug candidate for cancer therapy.